Diclofenac in hyaluronic acid gel: an alternative treatment for actinic cheilitis - LIMA, Giana da Silveira (J Appl Oral Sci, 2010)
OBJECTIVE: Actinic cheilitis (AC) is a precancerous lesion of the lip vermillion caused by prolonged exposure to ultraviolet light. The aim of this study was to evaluate the effect of 3% diclofenac in 2.5% hyaluronic acid gel in the treatment of AC. METHODS: Thirty-four patients with chronic AC were treated twice a day with topical diclofenac during a period of 30 to 180 days. The individuals were followed up every 15 days by means of clinical examination and digital photographic documentation. RESULTS: Of the 27 patients that completed the study, 12 (44%) showed complete remission of the whitish plaques and exfoliative areas, and 15 (56%) had partial remission of the clinical picture of cheilitis. The latter group was submitted to excision of the leukoplakic areas which diagnosis varied from mild to moderate epithelial dysplasia. CONCLUSION: The results suggest a promising role for diclofenac in hyaluronic acid gel in the treatment of AC. This treatment has the advantages of not being invasive and showing few side effects.